PERALIHAN RISIKO DALAM JUAL BELI ONLINE MENURUT WAHBAH ZUHAILI DAN HUKUM POSITIF - Miftah, Zaini; Sarwini, Ahmad; Chusanti, Dima; Abrori, Muhammad (Information Technology and Science (ITScience), 2025)
Latar belakang: The development of information and communication technology has brought significant changes in the way people transact, one of which is through online buying and selling. Although it offers convenience, this transaction also presents various risks, especially in relation to the quality of the goods and the responsibility of the seller. In this context, an understanding of risk transfer in online buying and selling is very important, especially from the perspective of Islamic law and positive law. Wahbah Zuhaily, a prominent scholar, provides guidance on the rights and obligations in buying and selling transactions, including the right of khiyar for buyers if the goods received are not as promised. On the other hand, positive law, particularly the Civil Code (KUHPerdata), also regulates the seller's responsibility for the goods sold. Metode penelitian: To find out the answers to the problems above, this study is directed at Clinical Law research (Legal Research), this type of research aims to find legal provisions for concrete problems. The data analysis technique used is by collecting data related to the problem being studied using special rules, then analyzing it and drawing conclusions. Then, to complete this problem can be resolved with valid answers, a data collection instrument is used, namely interviews. Hasil penelitian: The research results show that many online shop sites are not responsible for defects in the goods promised. So, this is not in accordance with Islamic concepts or Fiqh and the Civil Code. In line with Wahbah Zuhaily's opinion in the Book of al-Fiqhu al-Islami Wa Adillatuh that if there is damage to an item being bought and sold, the buyer is given the khiyar right to continue the sale and purchase by paying for the item according to the defect or canceling the transaction. Likewise, in the Civil Code, responsibility for the risk of an item is still borne by the seller in accordance with Articles 1456, 1474 and 1491 of the Civil Code. Kesimpulan: If there is a risk in the goods being traded, the buyer has the khiyar right to continue the transaction by paying for the defective goods or cancel the sale. According to the Civil Code, title does not pass to the buyer until delivery is made (1459), and the seller is responsible for safe possession of the goods as well as hidden defects (1491). Online buying and selling can be analogized to salam buying and selling in fiqh muamalah.